Your total image - "Davies, Phillipa" (London, 1990)
It is claimed that people influence others, and are judged by them, through their appearance, voice, environment and manner more than by what they say. This book looks at various aspects of personal presentation, including posture, body and eye contact, voice, facial expression, use of territory, dress, decor and furniture and design of business stationery. It offers advice on how to succeed at meetings, presentations and interviews and how to create the right image when talking to the press or involved in work-related socializing. The author's aim is to provide, with the help of exercises and photographs, a guide for anyone who wants to succeed personally or professionally. She has her own business which trains key personnel of major companies in public speaking and self-presentation.
Keywords: Man Attitude and movement